LTSR MA Chemijos ir cheminės technologijos mokslinio tyrimo instituto elektrochemikų informaciniai poreikiai - Varnienė, Regina (Knygotyra, 2026)
The investigation of information needs in the Institute of Chemistry and Chemical Technology of Academy of Sciences Lit. SSR allowed to draw conclusions about sources of information necessary for researchers, forms of information supply for electrochemists and time needed for reading of scientific literature. Profile interests turned out too, they were brought together into "Rubricator of profile interests of the Institute". (List of headings).During the first stage we found out, that use of sources of information (except manuals, industrial catalogues, standards and translations) straightly depends on scientific qualification of specialist, on his duties.The higher are those indexes the more sources of information are used by specialists. The use of sources of information is influenced by the kind of the field in which scientist works.The use of sources of information dealing with literature (except the express information services, bibliographical catalog and encyclopedias) depends thoroughly on the scientific qualification of specialists, on their duties. The kind of the field in which the scientist works influences use of those sources.Forms of informational supply depend on scientific qualification of specialist: Doctors value analytical and abstract surveys (45,5). Scientists of this kind are interested in the guidance of librarians. Doctors need less help from scientific and technical information services and librarians in order to obtain factographical data.Great part of young scientists recognizes that serious part of informational supply is „guidance by librarians in the selection of information dealing with a special theme." 23,1 % specialists without scientific degree recognize this kind of assistance to be necessary. Analyses of results of questionnaires enables to draw a conclusion, that time, which is needed for selection and editing the collected literature depends on the duties and qualification. It was defined that researchers with high qualification spend more time for looking over and reading scientific literature in comparison with specialists without scientific degree.During the second stage of the investigation turned out profile interests of Institute scientists. Profile interests were brought together into „Rubricator". Its analysis enabled to define inner and outer relations between electrochemistry, galvanotechnics and other branches of science.According to the analysis of card file interests, the greatest part of electrochemists (72,3%) value part of "electrochemistry", second place occupies "electrochemical methods of protection", on the third – "technologies of organical material" (37,4).